2020
DOI: 10.1074/jbc.ra119.012019
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-98 reduces nerve growth factor expression in nicotine-induced airway remodeling

Abstract: Evolving evidence suggests nicotine may contribute to impaired asthma control by stimulating expression of nerve growth factor (NGF), a neurotrophin associated with airway remodeling and airway hyperresponsiveness (AHR). We explored the hypothesis that nicotine increases NGF by reducing lung fibroblast (LF) microRNA-98 (miR-98) and PPARγ levels thus promoting airway remodeling. Levels of NGF, miR-98, PPARγ, fibronectin 1 (FN1), endothelin-1 (ET-1), and collagen (COL1A1, and COL3A1) were measured in human LFs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 69 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…For example, miR-98 attenuates nicotine-induced airway remodelling by suppressing NGF. 14 In the current study, the expression of 78 miRs showed significant changes in nicotine-treated BECs in comparison with those in control BECs, which contributed to the alternatives in different biological functions. We selected let-7c-5p as a candidate target to mediate the function of CuE based on RT-qPCR detection.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…For example, miR-98 attenuates nicotine-induced airway remodelling by suppressing NGF. 14 In the current study, the expression of 78 miRs showed significant changes in nicotine-treated BECs in comparison with those in control BECs, which contributed to the alternatives in different biological functions. We selected let-7c-5p as a candidate target to mediate the function of CuE based on RT-qPCR detection.…”
Section: Discussionmentioning
confidence: 52%
“…Previous studies have demonstrated that the progression of airway remodelling is always associated with the down‐regulation of let‐7c‐5p 12,13,23 . Moreover, the downstream effector of let‐7c‐5p, NGF, is well characterized for its promotive effect on airway remodelling 14,24 . Thus, the level of let‐7c‐5p induced by CuE in nicotine‐treated BECs and mice may explain the protective effects of the compound: the up‐regulation of let‐7c‐5p contributed to the down‐regulation of NGF, which attenuated nicotine‐induced airway remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…In lung fibroblasts, the pro-fibrotic effects of NGF are inhibited because transforming growth factor-β1 (TGF-β1)-induced miR-455-3p limits the production of NGF [24]. Moreover, the increase in the levels of NGF and other markers of nicotine-induced airway remodeling is negatively regulated by miRNA-98 [25]. Overexpression of miR-221 is related to maximal downregulation of NGF and its TrkA receptor at both the mRNA and protein levels [26].…”
Section: Ngf and Affected Pathways In Lung Diseasesmentioning
confidence: 99%
“…A well-known cause of asthma is exposure to nicotine. Human primary lung fibroblasts from smokers and mouse primary lung fibroblasts from mice exposed to nicotine both show reduced PPARγ protein levels [ 87 ]. In the nicotine-exposed mice, treatment with the PPARγ pathway activator rosiglitazone restores the expression level of miR-98, a miRNA that negatively regulates the expression of airway remodelling proteins associated with collagen deposition and fibrosis [ 87 ].…”
Section: The Pparα and Pparγ Epigenetic Landscape In Diseasementioning
confidence: 99%
“…Human primary lung fibroblasts from smokers and mouse primary lung fibroblasts from mice exposed to nicotine both show reduced PPARγ protein levels [ 87 ]. In the nicotine-exposed mice, treatment with the PPARγ pathway activator rosiglitazone restores the expression level of miR-98, a miRNA that negatively regulates the expression of airway remodelling proteins associated with collagen deposition and fibrosis [ 87 ]. Similarly, pioglitazone-mediated PPARγ activation in rats inhibits airway smooth muscle cell proliferation and remodelling by supressing the Smad-TGFβ1-miR-21 signalling pathway [ 88 ].…”
Section: The Pparα and Pparγ Epigenetic Landscape In Diseasementioning
confidence: 99%